Patterns and correlates of substance use among young adult African American women. Issue 1 (1st March 2022) - Madkour, Aubrey Spriggs; Clum, Gretchen; Green, Jakevia; Latimer, Jen; Schmidt, Norine; Johnson, Carolyn; Kissinger, Patricia
Abstract: Patterns and correlates of substance use among urban African American young women (ages 18–19, n = 459) were examined. Four patterns were identified: no/infrequent alcohol and marijuana use (64.9%); recent alcohol only use (18.2%); recent marijuana only use (7.9%); and recent alcohol and marijuana use (9.0%). Having a recent male sexual partner and a history of sexual coercion were associated with increased odds of marijuana-only and dual use. Greater family support and childhood sexual abuse were associated with increased odds of alcohol-only use. Results suggest that sexual relationships and history of abuse/coercion are important factors in young African American women's substance use.